2018
DOI: 10.18203/2320-1770.ijrcog20182863
|View full text |Cite
|
Sign up to set email alerts
|

Decision to incision interval for emergency caesarean section and postoperative outcomes in a resource limited rural Kenyan public hospital

Abstract: Background: Standard guidelines recommend that delivery by caesarean section should be ideally initiated within 30 minutes of the decision to operate to avoid maternal and foetal compromise in labour. The purpose of this study was to investigate the extent to which these guidelines can be achieved in limited resource hospital.Methods: Authors used a secondary data from 330 patient's files of women who had a caesarean section from December 2013 retrospectively to January 2012.Results: The main indications for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
5
2
Order By: Relevance
“…In this study, women who were transferred to the operating room before 15 min showed a statistically significant association with recommended DDI than women who were transferred after 15 min. This finding was consistent with study findings in India, Nigeria, Kenya, and Gondar, Ethiopia [ 9 , 10 , 19 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, women who were transferred to the operating room before 15 min showed a statistically significant association with recommended DDI than women who were transferred after 15 min. This finding was consistent with study findings in India, Nigeria, Kenya, and Gondar, Ethiopia [ 9 , 10 , 19 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy may be due to a lack of funds for surgical materials and the absence of post-service billing in the study area of Nigeria, as patients’ relatives usually pay surgical fees before the operation is performed. The findings of this research were also greater than those of studies conducted in Tanzania and Kenya, which were 12 and 3%, respectively [ 8 , 10 ]. The difference may be that studies in both countries were conducted before the initiation of saving lives through the SaLTS) initiative in East Africa, which was started in late 2016.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Contrary to our findings, elsewhere in Nepal, a country with similar economic conditions as Tanzania but considerably lower gross domestic product per capita compared to Kenya, a significant reduction of neonatal mortalities, including CD-related, has been found [57]. To highlight the difference, for instance, a comparison can be made between two parallel studies [58,59] from matching district-level hospitals with similar year of data collection and numbers of cesarean deliveries (330 vs 327) in Kenya [58] and Nepal [59]. The majority (43%) of patients in Nepal hospitals were of disadvantaged lower caste comparable to patients in the refugees`area in northeastern Kenya.…”
Section: Discussioncontrasting
confidence: 92%
“…To save lives when obstetric and newborn complications arise, women should receive definitive treatment within 30 min or less. 24 25 The standard approach if complications arise during childbirth in primary care settings is to refer women to hospitals. However, transporting acutely ill patients is challenging even in high-income settings with fully equipped advanced life support ambulances, reliable communication and good roads.…”
Section: Revisiting the Assumptions Of The Current Model Of Carementioning
confidence: 99%